Organochlorine Contaminants in Maize Fertilized with Meat and Bone Meal Derived from Animal By-Products - Arkadiusz Stępień; Katarzyna Wojtkowiak; Ewelina Kolankowska; Renata Pietrzak-Fiećko (Applied Sciences)
Despite the fact that organochlorine pesticides (OCPs) were banned many years ago, their residues are still present in the natural environment and pose a potential health risk to humans and animals. This study was undertaken to evaluate the effect of meat and bone meal (1.0, 2.0 and 3.0 t ha−1 MBM) derived from animal by-products and used as fertilizer on the content of γ-HCH (γ-hexachlorocyclohexane), DDT (1,1,1-Trichloro-bis-2,2 [4-chlorophenyl]-ethane) and its metabolites (DDD, dichlorodiphenyldichloroethane and DDE, dichlorodiphenyldichloroethylene) in MBM, soil, and maize grain. A long-term small-area field experiment with MBM applied to maize grown in monoculture was conducted at the Agricultural Experiment Station in Tomaszkowo, Poland (53°71′ N, 20°43′ E) from 2014 to 2017. The concentration of γ-HCH in soil decreased gradually, whereas the levels of DDT and its metabolites continued to increase in successive years of the experiment. A minor increase in DDT accumulation in maize grain was also observed, particularly in treatments supplied with mineral fertilizers. Meat and bone meal affected grain contamination levels, and the highest MBM rates decreased the content of DDT metabolites in grain. The results of the study suggest that MBM could be a secondary source of OCPs in the agricultural environment and that their availability to plants varies depending on soil parameters and weather conditions.